Recensiones - S. de Anitua; Mantilla, Sebastián; S. M.; Montes, Santiago; I. C.; I. M. B.; Casín, Isabel (ECA: Estudios Centroamericanos, 1971)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 26, No. 272, 1971: 356-368.